2021
DOI: 10.1111/are.15366
|View full text |Cite
|
Sign up to set email alerts
|

Citrullus colocynthis extract and synthesized Selenium nanoparticles enhance non‐specific response and resistance against Aeromonas sobria in Nile tilapia ( Oreochromis niloticus )

Abstract: Nile tilapia is a cornerstone of fish farming in Egypt, which is the largest aquaculture producer in Africa. With 900,000 tons of tilapia harvested annually, the country has risen to become the seventh aquaculture producer in the world (Feidi, 2018). The progress of this fast-growing industry is impeded by many challenges such as poor water quality and associated bacterial infections (El-Gohary et al., 2020). As a result, the use of antibiotics in the aquafeeds to mitigate infectious diseases or to boost growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…It has been reported in earlier studies that Labeo rohita , and Oreochromis niloticus which received 0.3 mg/kg, and 1-2 mg/kg of SeNPs supplemented diets, respectively enhanced myeloperoxidase, respiratory burst, and lysozyme activity [43] . The dietary supplementation of 2 mg/kg SeNPs for 30 days in Oreochromis mossambicus significantly enhanced myeloperoxidase, respiratory burst, and lysozyme activity [91] . Moreover, the polysaccharides isolated from Porphyra yezoensis , and Ficus carica have also been reported to significantly ( p ˂ 0.05) improved serum lysozyme activity in grass carp and crucian carp, respectively [ 92 , 93 ].…”
Section: Resultsmentioning
confidence: 89%
“…It has been reported in earlier studies that Labeo rohita , and Oreochromis niloticus which received 0.3 mg/kg, and 1-2 mg/kg of SeNPs supplemented diets, respectively enhanced myeloperoxidase, respiratory burst, and lysozyme activity [43] . The dietary supplementation of 2 mg/kg SeNPs for 30 days in Oreochromis mossambicus significantly enhanced myeloperoxidase, respiratory burst, and lysozyme activity [91] . Moreover, the polysaccharides isolated from Porphyra yezoensis , and Ficus carica have also been reported to significantly ( p ˂ 0.05) improved serum lysozyme activity in grass carp and crucian carp, respectively [ 92 , 93 ].…”
Section: Resultsmentioning
confidence: 89%
“…The authors correlated the enhanced growth performance with the role of Se nanoparticles in activating the protease, thereby feed utilization. In several feeding trials that lasted for 4 to 8 weeks, Nile tilapia (Oreochromis niloticus) fed dietary nano Se at 1-2 mg/kg showed enhanced growth performance and feed utilization [25,[52][53][54][55]. Notably, Abd El-Kader et al [56] and Abd El-Kader et al [57] reported that European seabass (Dicentrarchus labrax) fed Se nanoparticles at 0.5-1 mg/kg had enhanced growth performance and feed efficiency.…”
Section: The Role Of Selenium Nanoparticles On the Growth Performancementioning
confidence: 99%
“…In another study, Dawood et al [68] concluded that Se nanoparticles resulted in the increased alternative complement pathway, nitro blue tetrazolium activity (NBT), total serum protein, bactericidal activity, lysozyme activity, and skin mucus secretions in red sea bream. In Nile tilapia, Ayoub et al [53] reported enhanced serum lysozyme and respiratory burst activities by dietary Se nanoparticles (1-2 mg/kg). Further, Abu-Elala et al [54] and Ghazi et al [55] reported that Nile tilapia-fed dietary Se nanoparticles (1-2 mg/mg) showed enhanced phagocytic, lysozyme activities, phagocytic index, red blood cells, globulin, and immunoglobulin M. In European seabass, Abd El-Kader et al [56] and Abd El-Kader et al [57] reported increased hemoglobin, hematocrit, red blood cells, white blood cells, total serum protein globulin, phagocytic index, phagocytic, and lysozyme activities by dietary Se nanoparticles (0.5-1 mg/kg).…”
Section: Effect Of Selenium Nanoparticles On the Immunological Biochemical And Hematological Parameters Of Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the emergence of antimicrobial resistance (AMR), which threatens all sectors of production, including animals and aquaculture, the World Organization for Animal Health (OIE) and Food and Agriculture Organization (FAO), with the assistance of the World Health Organization (WHO), launched a plan to reduce the use of synthetic antimicrobials (WHO, 2015), opting instead for the use of natural products as safe alternatives to antimicrobials. Antimicrobial alternatives with improved efficacy in aquaculture include herbal compounds (Ayoub et al, 2019; Ayoub et al, 2021; Abdelhamid et al, 2021; Ashour et al, 2020; Dawood et al, 2021; Negm et al, 2021) as well as macro‐ and microalgae (Mayer & Hamann, 2005). Microalgae are ubiquitous unicellular organisms that grow in all aquatic environments (de Morais et al, 2015), and their antimicrobial activity is related to the presence of terpenes, indoles, acetogenins, phenols, volatile halogenated hydrocarbons, and fatty acids (Cardozo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%